France 1940 : blitzkrieg in the West - Shepperd, Alan. (London : Osprey, 1990)
"The German victory of 1940 stunned the world. France, major European power and owner of one of the World's largest armies had fallen in less than seven weeks to the might of the German Wehrmacht. The secret of the Wehrmacht's success lay in its carefully thought out organisation and the tactics of blitzkrieg. Fast moving tank divisions supported by armoured, mobile infantry swept over the opposition, helped by both conventional bombers and deadly Stuka dive-bombers. Alan Shepperd's highly detailed text examines the tactics, organisation and equipment of the Allied and German forces, and provides a daily account of the most crucial period of the battle"--Page 4 of cover.
Background for war -- The opposing commanders. The French commanders -- The German commanders -- The opposing armies. Forces engaged -- Air Forces -- Morale -- The opposing plans. French strategy -- German strategy -- The battle for France. 10 May -- 11 May -- 12 May -- 13 May : over the Meuse -- 14 May -- 15 May : German exploitation -- 16 May -- 17 May -- The general scene: 16 and 17 May -- 18 to 23 May -- Dunkirk -- The result.
Includes bibliographical references (p93).
Keywords: 1900-1999; World War, 1939-1945 -- Campaigns -- France; Lightning war -- History -- 20th century; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- France; x; Lightning war; Military campaigns; Westfeldzug; World War, 1939-1945 -- Campaigns -- France; France; France, 1939-1945; History